Personal Branding Strategies on Social Media Platforms (Case Study of Gaming YouTuber Ari Kulgar and Badminton Influencer @bernika_ave) - Scheffer-Sumampouw, Carly Stiana; Serafin, Michelle; Fortuna, Christabella Angelique (Communicare : Journal of Communication Studies, 2024)
Booming profession is intensively utilizing social media on the internet. Choice of job or career as gamer and influencer, is very popular among the young generation of Indonesia. This activity of promoting oneself through social media is called personal branding. This study discusses two subjects who have different careers, but both use social media intensively in their career journeys. The two selected key informants have fulfilled the category of unique and prominent influencers in their industries. The theory used is about impression management by Erving Goffman; then how Montoya's 8 laws of personal branding are applied by both subjects. Study limitations are that the researchers only discuss the "front stage" aspect. While the "backstage" aspect is not discussed, even though this aspect feels the most honest. The method used is a case study, while the main data is obtained through interviews, field observations and of course social media observations. The results of the study show that two different social media have their respective roles and are indeed very distinctive and appropriate to serve these two different types of industries. A gamer prefers YouTube, while an influencer choose TikTok, each to build their personal brands.